Anti-microbial activities and phytochemical screening of some commonly used chewing sticks in Kano, Nigeria - Umar, A. B.; Dankaka, A. H.; Shah, M. Manjur (Horticultural Biotechnology Research, 2020)
This research work was aimed to determine the antibacterial activity of aqueous and ethanolic extract of plants commonly used in Kano on a clinical isolate of Staphylococcus and Streptococcus species obtained from the dental problem with a view to find the most efficacious one among them. The sensitivity disc method was used to test the antibacterial activity of chewing sticks, Eucalyptus globulus, Salvadora persica, Gledistsia triacanthos, Azadirachta indica and Jatropha curcas were the plants. It was found that none of the plants ‘aqueous extract had activity on the two species of the bacterial isolate at various concentrations. But ethanolic extract was active against all the test bacterial isolate obtained from the dental problem with a greater zone of inhibition in A. Indica, followed by E. globulus and a smaller zone of inhibition in J. curcas. Some of the secondary metabolites were all present with high content in ethanolic extract. The extracts of these plants may serve as sources for chemotherapeutic agents of the management of orofacial infection.